From occupation to independence: contemporary East Timorese history and identity in Portuguese picturebooks - Ana Margarida Ramos (Problemy Wczesnej Edukacji, 2016)
In Portugal, the suffering and struggle of the East Timorese people for independence started a social movement of solidarity with strong repercussions in the arts, namely music and literature. Children’s Literature depicted the theme of this period of oppression in East Timor, as well as the recognition of its independence and its right to freedom, in a picturebook selected for the White Ravens List in 2003 called East Timor – Island of the Rising Sun (2001), by João Pedro Mésseder and André Letria. This unusual picturebook, characterised by a very simple and sparse, almost poetic, text combined with large-format pictures, depicts this chapter of the contemporary history of East Timor in very specific way, resembling fairy tales or legends. The text and images are combined in order to promote symbolic readings, suggesting a magical/mystical environment that impresses readers. More than a decade later, recent struggles and stories from East Timor are still present in Portuguese picturebooks such as Lya/Lia (2014), by Margarida Botelho. The social change, path to democracy and educational development, as well as daily life and children’s pastimes are now the centre of a narrative that establishes the similarities and differences between modern-day Portugal and East Timor. Our aim is to analyse both the political and ideological perspectives present in these picturebooks aimed at very young readers, offering a broad vision of different realities and contexts, even when they deal with war, death and suffering, as was the case of the East Timorese fight for independence.